Assessing and modeling economic and environmental impact of wheat nitrogen management in Belgium. (May 2016) - Dumont, B.; Basso, B.; Bodson, B.; Destain, J.-P.; Destain, M.-F.
Abstract: Future progress in wheat yield will rely on identifying genotypes and management practices better adapted to the fluctuating environment. Nitrogen (N) fertilization is probably the most important practice impacting crop growth. However, the adverse environmental impacts of inappropriate N management (e.g., lixiviation) must be considered in the decision-making process. A formal decisional algorithm was developed to tactically optimize the economic and environmental N fertilization in wheat. Climatic uncertainty analysis was performed using stochastic weather time-series (LARS-WG). Crop growth was simulated using STICS model. Experiments were conducted to support the algorithm recommendations: winter wheat was sown between 2008 and 2014 in a classic loamy soil of the Hesbaye Region, Belgium (temperate climate). Results indicated that, most of the time, the third N fertilization applied at flag-leaf stage by farmers could be reduced. Environmental decision criterion is most of the time the limiting factor in comparison to the revenues expected by farmers. Highlights: The economic and environmental impact of Nitrogen fertilization was evaluated. A complete and generic methodology for tactical N optimization is proposed. Climatic conditions occurring between sowing and flag leaf stage greatly impacts N optimization. Environment × management interactions have to be considered when optimizing N. Environmental consideration is a more limiting factor than expected revenues for N optimization.